Kinetic and mechanistic study of substitution on a cytotoxic PtII complex with biologically relevant thiols and a density functional study. (28th May 2017) - Mitra, Ishani; Reddy B., Venkata P.; Mukherjee, Subhajit; Moi, Sankar Ch.
Graphical abstract: An associative substitution path was proposed for the interaction of a cytotoxic Pt(II) complex with bio-relevant ligands through kinetic and mechanistic investigations along with DFT computations. Abstract: A systematic investigation of the interactions of platinum antitumor complexes with sulfur-containing biomolecules is of paramount importance to gain an insight into platinum metabolism. To this effect, the rate of substitution of aqua ligands by biologically relevant nucleophiles, l -cysteine (l -cys) and N-acetyl-l -cysteine (NALC), for the complex [Pt(AMBIM)(H2 O)2 ] 2+ (where AMBIM = 2-aminomethylbenzimidazole) was investigated under pseudo-first-order condition as a function of concentration and temperature by UV/Visible spectrophotometry. The reaction proceeded in two consecutive steps; the first being a ligand-assisted anation followed by a chelation step. The activation parameters (ΔH ǂ and ΔS ǂ ) for both the steps have been evaluated using Eyring equation, which suggest an associative mode of activation for both the displacement processes. The kinetic study was substantiated by spectroscopic results and density functional theory (DFT) calculations such as NBO analyses. Time dependent DFT (TD-DFT) was also performed to comprehend the nature of the electronic transitions in the product complexes. Global reactivity parameters were incorporated to unravel the reactivity of the Pt-S adducts towards potential targets such as nucleobases.